Sustaining respecting patient choices® (RPC) advance care planning. Issue 2 (1st June 2012) - Hunt, R; Jones, L; Owen, L; Seal, M
Abstract : The Central and Northern Adelaide Local Health Networks in South Australia (SA) oversee four major hospitals and a range of sub-acute and primary health care services. The Respecting Patient Choices (RPC) Program has been rolled out progressively across the two Networks, in parallel with the country Network, by a Project Team. The Project has worked towards embedding Advance Care Planning (ACP) and appropriate use of advance care plans across the health continuum. It has focused on supporting organisations through: training; developing system support and accessible resources; strengthening partnerships; and facilitating strong leadership in ACP. The lessons from this project have been integrated into a state-wide model for ACP which includes: the establishment of an RPC Trainer/Liaison position to support trainers Statewide; and aims to have a network of RPC Portfolio Leads in organisations responsible for maintaining ACP development. In SA over 2, 500 RPC Facilitators are trained across ∼250 organisations including acute, GP Divisions, aged care, and community services. The Program has brought about improvement in ACP. For example: within 67 organisations, over 1400 patients are registered with ACP hospital Alerts, with an estimated 1600 created in the community above base line in 12 months. RPC in SA is assisted by effective legislation, Consent to Medical Treatment and Palliative Care Act 1995, producing policy that enables health workers to honour ACP. RPC is bringing to effect SA's Health Care Plan commitment to provide ACP as part of appropriate care to the older person and transmission to a sustainable model is underway.